Study on phase change material thermal characteristics during air charging/discharging for energy saving of air-conditioner - Songheng Loem (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. In this study, RT-18 HC phase change material (PCM) having a melting point at 18 °C in a form of packed bed was used to reduce the power consumption of a 1 TR inverter air conditioner. A set of spherical balls was packed and integrated with the air conditioner for reducing the air temperature before entering the evaporator coil. The enthalpy method was developed for calculating the PCM temperatures and verified by testing results. The operating parameters such as bed thickness, air mass flow rate, inlet air temperature, operating time and properties of air and PCM during charging and discharging modes were also correlated in dimensionless forms. With the correlations, the charging and the discharging modes for three PCM bed thicknesses: 0.08 m, 0.16 m, and 0.24 m were evaluated, and it could be found that the results from the correlations agreed well with those from the experimental data within ±6% deviation. In addition, the electrical power consumptions of the air conditioner with these integrated PCM beds were 4.96 kWh/d, 4.7 kWh/d and 4.34 kWh/d compared with 5.04 kWh/d of the normal unit or 1.58, 6.80 and 13.84% of electrical energy could be saved, respectively.